Green finance and green growth: towards sustainable development in South Africa - Chinyamunzore, Ephraim (Graduate School of Business (GSB), 2019)
The economic progress that the world has achieved so far, has come at a steep price to the environment and social justice. There is a general global rise in environmental degradation and social inequality, mainly due to unsustainable habits of production and consumption. Greenhouse gas emissions, primarily from burning fossil fuels, are on the rise; causing global warming, climate change, and the resultant extreme weather conditions. This global trend is also manifesting itself in South Africa; where the current economic model has failed to adequately address unemployment, poverty, and inequality. Several studies have recommended that countries should implement the Green growth strategy as a solution, because it will move economies towards sustainable development. Greening economies require investments in low carbon infrastructures, such as Renewable Energy (RE) technology, and supportive policies. The purpose of this study is to explore South Africa’s RE policy instrument and the country’s progress towards green growth. To this end, correlation analysis was used to investigate the relationship between green finance and South Africa’s RE policy instrument; descriptive statistical analysis was employed to investigate South Africa’s progress towards green growth. Other BRICS countries as well as Germany were included in order to benchmark South Africa’s progress. The study found a positive correlation between green finance and the RE policy instrument. The implication of this finding is that reductions in tariffs paid to RE producers, due to the auction process, may result in decreased levels of green finance invested in the RE sector. A policy recommendation would be to include other financial incentives to attract investments in the RE sector, such as favourable tax rates for producers and the use of subsidies. Another finding is that there was a tendency for private finance invested in these projects to decrease as the level of public finance increases, suggesting crowding out. Policy recommendations are that public finance should be restricted to small projects; play a subordinated role in big projects; and address investment difficulties faced by private investors. The following are some of the findings with regard to South Africa’s progress towards green growth. South Africa was the second worst CO2 emitter per capita; recorded high levels of air pollution; was one of the least energy-efficient countries; regressed on forests management and had the lowest percentage of RE consumption. The implications are negative for the country’s progress towards green growth. The suggested solutions are to promote energy efficiency and increase RE consumption by accelerating green investments in the RE sector. There is hope though, that South Africa is making good progress towards sustainable development, as depicted by the growth rates of most of the country’s green growth indicators.